UPAYA PENINGKATAN KEMAMPUAN MEMAHAMI SIFAT-SIFAT OPERASI HITUNG BILANGAN MELALUI METODE PEMBELAJARAN FRIEND GIVING SISWA KELAS IX-E MTS NEGERI REJOSARI KABUPATEN MADIUN TAHUN PELAJARAN 2011/2012 - Emy Widiastuti (Jurnal Penelitian LPPM (Lembaga Penelitian dan Pengabdian kepada Masyarakat) IKIP PGRI MADIUN, 2015)
Mathematics as problem solving activities, The implication of this point of view for mathematics teachers need to: (1) providing a learning environment mathematics to stimulate the emergence of mathematical problem, (2) help students solve math problems using its own way, (3) help the students to know the information needed to solve a mathematical problem, (4) encourages students to think logically, consistently, systematically and develop a system of documentation / records, (5) developing the capacity and skills to solve problems, (6) help the students to know the way of using mathematics media such as: compass, ruler, calculator, etc. Friend giving method is a method of learning that are interesting to the students because students can learn in a serious but relaxed. The problem statement of the research: Is there an ability increasing in using and understanding the properties of arithmetic operations of numbers in solving problems through friend giving students of class IX-E MTS Foreign Rejosari Madiun in the Schooling Year 2011/2012?  The approach used in this study is Classroom Action Research with quantitative approach. In this study, researchers collaborate with other teachers and the principals. Researchers involved in the study from the beginning to the end of the study. Researcher is trying to see, observe, feel, live, reflect and evaluate learning activities. The stages of research consist of planning, acting, observing and reflecting. The study collected data were statistically analyzed using the formula that is mean or average to get accurate results. The result showed that the average value of 77.23 in the first cycle and the second cycle obtained by the average value of 86.92. Referring to the hypothesis that the actions proposed in this Classroom Action Research it can be concluded that: there is an increased ability to understand the properties of arithmetic operations of numbers and their use in solving problems with learning friend giving students of class IX-E MTS Rejosari Madiun in the Schooling Year 2011/2012.